Bilingual Education during a Pandemic: Family Engagement. La educación bilingüe durante una pandemia: compromiso familiar - Victor Antonio Lozada; Holly Hansen-Thomas; Jorge Figueroa; Mary Amanda Stewart (Universidad de Las Palmas de Gran Canaria, 2022)
During the COVID-19 global pandemic, teachers have had to be creative on how they engage with the families of emergent bilingual students. This content analysis of four teacher focus groups reveals ways in which teachers have worked to connect with their students over a distance. The purpose of this paper is to discover, from educators, effective teaching strategies that engage families and emergent bilinguals during the COVID-19 pandemic and online teaching. Resulting themes included technology in teaching, building relationships with families, and accessing the educational assets of emergent bilinguals and their families. Connections to cariño (Bartolomé, 2008), educación (Valenzuela, 1999), and using the term 'emergent bilingual' (García, 2009) are discussed.